Design of a Blockchain-Based Smart Contract Model for Child Labor Alleviation - Senou, Mahugnon Rosaire Brice; Degila, Jules (My University, 2020)
The achievements of west and central Africa in producing more than 60% of the world’s cocoa, and sub-Saharan Africa’s achievement in producing 13% of the world’s cotton, hide child labor. These significant levels of production often involve child exposure to issues such as a lack of education; pesticides; dangerous farming tools; work accidents; human trafficking; etc. Blockchain offers an immutable register that allows for digital transactions, smart contract creation, as well as end-to-end product traceability. The main aim of this article is to provide an intelligent contract framework that protects child labor in farming while further enlightening understandings of adoption-related challenges. This framework considers conditions that farmer associations need to satisfy and gives them a tool to improve children’s welfare. A research model for the adoption of this tool has been proposed and validated through surveys in the cotton and cacao sectors.
Keywords: Acceptation Issues; Blockchain; Central Africa; Child Work; Cocoa; Cotton; Digital Ledger; Intelligent Agreement; Investigation; West Africa